Marzolph, Ulrich (2020): 101 Middle Eastern Tales and Their Impact on Western Oral Tradition, Detroit, Wayne State University Press, 706 pp. - López Bernal, Desirée (Boletín de Literatura Oral, 2021)
Reseña de: Marzolph, Ulrich (2020): 101 Middle Eastern Tales and Their Impact on Western Oral Tradition, Detroit, Wayne State University Press, 706 pp.